Kenabian di dalam Cerpen Ra’i al-Ganam Karya Thaha Husein: Analisis Semiotika Charles Sanders Pierce / Prophethood in The Short Story "Ra'i al-Ganam" by Thaha Husain: Charles Sanders Pierce 'S Semiotics Analysis - Futaqi, Mirza Syauqi; Amanah, Tazkiyyatul (Diwan: Jurnal Bahasa dan Sastra Arab, 2021)
تهدف هذه المقالة إلى كشف ومعرفة العلامات المتعلقة بنبوة محمد باعتباره شخصية رئيسية في القصة القصيرة “راعي الغنام”. لكشف معنى العلامات المتعلقة بنبوة محمد، استخدم الباحثان نظرية السيميائية لتشارلز ساندرز بيرس، والمنهج الوصفي التحليلي، والنهج الموضوعي. رأى بيرس العلامة على أنها تحتوى على العلاقة الثلاثية: التمثيل والموضوع والمفسر. سيركز الباحثان على العلاقة بين الممثل والموضوع لأن بروس يرى أن هذه العلاقة أهم علاقة وأكثر أساسيا من غيرها. وتتكون تلك العلاقة من العلاقة الأيقونة والعلاقة القرينة والعلاقة الرمزية. وأما نتيجة البحث فتشير إلى أن النبوة في القصة القصيرة “راعي الغنام” سر من أسرار الله وغير مكتسبة لايعرفها إلا الله. لا أحد يستطيع أن يعرف النبوة ويفهمها تمامًا. ومع ذلك، هناك العديد من علامات النبوة التي يمكن فهمها من خلال العقل. ومحمد باعتباره نبيا في القصة يكون صورة مثالية لأمته وله أيضًا ثلاث خصائص (قوة التخيل وقوة النظرية وقوة النفس). الكلمات المفتاحية: النبوة; العلاقة الثلاثية; الأيقونة; القرينة; الرمزية. Abstract: This article aims to reveal and know the meaning of the signs relating to the prophethood of Muhammad as the main character in the short story Ra’il Ganam. In order to reveal the meaning of the sign associated with Muhammad's prophethood, the researcher uses Charles Sanders Pierce's semiotics theory, analytical descriptive method, and objective approach. Peirce sees sign as a triadic structure, representament, object, and interpretant. The researcher will focus on representament relation with object namely icons, indices and symbols because the relation, according to Pierce, is the most fundamental part of the sign. This study resulted that the prophethood in the short story Ra'il Ganam is the secret of God and cannot be achieved by human effort. No creature can know and understand it perfectly. Muhammad as a prophet in the short story became an ideal human being for people and also has three features (the power of imagination, the power of vision, and the power of the soul).